Species of Horismenus Walker (Hymenoptera: Eulophidae) associated with bruchid beetles (Coleoptera: Chrysomelidae: Bruchinae), including five new species - Hansson, Christer; Kenyon, Sarah G.; Benrey, Betty (Zootaxa, 2019)
Species of Horismenus Walker associated with bruchid beetles are investigated and five new species are described. Some of the new species are very similar to already described species and have previously been misidentified. The new species include H. depressoides sp. nov. similar to H. depressus Gahan , H. stator sp. nov. similar to H. missouriensis (Ashmead), and H. dennoi & H. multistriatus spp. nov., both similar to H. butcheri Hansson & Aebi and one species, H. gabrielae sp. nov., that is morphologically distinct from the other species but also associated with this host group. All 14 Horismenus species associated with bruchid beetles are included in a key. New host and distributional records are included for H. depressus.